Echoes from an irradiated disc in GRO J1655-40 - Hynes, R; O'Brien, K; Horne, K; Chen, W; Haswell, C (1998)
We demonstrate correlated rapid variability between the optical/UV and X-ray emission for the first time in a soft X-ray transient, GRO J1655-40: Hubble Space Telescope (HST) light curves show similar features to those seen by the Rossi X-ray Timing Explorer (RXTE), but with mean delay of up to 10-20 s. We interpret the correlations as the result of reprocessing of X-rays into optical and UV emission, with a delay owing to finite light travel time, and thus perform echo mapping of the system. The time-delay distribution has a mean of 14.6 ± 1.4 s and dispersion (i.e. the standard deviation of the distribution) of 10.5 ± 1.9 s at binary phase 0.4. Hence we identify the reprocessing region as the accretion disc rather than the mass donor star.